A method for preparing a structural / electromagnetic shielding integrated hybrid composite material

By growing zinc oxide nanowires on the surface of high-quality graphene three-dimensional networks and laid with carbon fiber cloth, a multi-scale hybrid composite material with high electromagnetic shielding performance and excellent mechanical properties was prepared, which solved the problem of insufficient electromagnetic shielding performance and mechanical properties of existing materials.

CN115594945BActive Publication Date: 2025-04-18INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211262122.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-14
Publication Date
2025-04-18
Estimated Expiration
2042-10-14

AI Technical Summary

Technical Problem

The electromagnetic shielding performance of existing carbon fiber reinforced resin-based composite materials is insufficient, which cannot meet the high-performance needs in military equipment, aerospace and other fields, and its mechanical properties are also insufficient.

Method used

A high-quality graphene three-dimensional network is used as the basic structural unit to grow zinc oxide nanowires on its surface to form a zinc oxide/graphene three-dimensional network hybrid composite material, and laminate it with a carbon fiber cloth, and then mold it through resin infusion to obtain a layered multi-scale hybrid composite material with a high-oriented structure.

Benefits of technology

The electromagnetic shielding performance and mechanical properties of carbon fiber composite materials have been improved simultaneously. The electromagnetic shielding performance is between 40dB and 70dB and the absorption performance is 30dB to 50dB. The mechanical properties including tensile strength, bending strength and interlayer shear strength are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003891491030000011
    Figure HDA0003891491030000011
  • Figure HDA0003891491030000012
    Figure HDA0003891491030000012
Patent Text Reader

Abstract

The present invention relates to the field of structural / functional composite materials, and specifically to a method for preparing a structural / electromagnetic shielding integrated hybrid composite material. A high-quality graphene three-dimensional network is used as a basic building unit, zinc oxide nanowires are grown on its surface, and a multi-scale hybrid composite material is obtained, which is then stacked and laid with carbon fiber cloth, and resin infusion molding is performed to obtain a layered multi-scale hybrid composite material with a highly oriented structure. The present invention gives full play to the significant advantages of high conductivity, large effective reflection area, and flexibility and light weight of high-quality continuous graphene three-dimensional networks, combined with the excellent dielectric loss characteristics and micro-nano structural characteristics of zinc oxide nanowires, and obtains a multi-scale hybrid composite material with both high shielding effectiveness and excellent mechanical properties through structural arrangement orientation and interface regulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of structure / functional composite materials, and in particular to a method for preparing a structure / electromagnetic shielding integrated hybrid composite material. Background Art

[0002] The rapid development of electronic communication technology and equipment has brought convenience to daily life, but it has also inevitably generated a large amount of electromagnetic radiation. In the fields of communications, medical care, aerospace, and military equipment, a series of problems such as electromagnetic interference and information security leakage caused by radio frequency equipment have not only seriously interfered with the normal operation of precision equipment, but also posed a huge threat to human health. To this end, it is of great significance to develop new lightweight and high-performance structural / electromagnetic shielding integrated materials. In recent years, carbon fiber reinforced resin-based composites have received extensive attention in the field of structural / electromagnetic shielding integration research due to their many superior properties such as low density, high specific strength and high specific modulus. Although carbon fiber has a certain conductivity, the electromagnetic shielding effectiveness of its composite material is still only 15dB~20dB, which cannot meet the growing performance requirements and greatly limits its application in military equipment, aerospace and other fields. Therefore, how to improve the electromagnetic shielding performance of carbon fiber reinforced resin-based composites has become a key scientific problem that needs to be solved urgently.

[0003] At present, there are three main methods to improve the electromagnetic shielding performance of carbon fiber reinforced resin-based composite materials:

[0004] One method is to add metal powder, magnetic particles, carbon-based conductive particles, etc. to resin to prepare functional composite materials, and achieve effective shielding of electromagnetic waves through the mechanism of dielectric loss and magnetic loss. However, traditional metal powder and magnetic particles have high specific gravity and poor compatibility with resin. Their composite materials generally have problems such as high density, low mechanical strength, and insignificant improvement in electromagnetic shielding performance, which cannot meet the urgent demand for high-performance materials in the military, national defense, and aerospace fields.

[0005] Another method is to enhance the surface conductivity and magnetic permeability of carbon fibers by depositing metal or nano-carbon conductive coatings on the surface of carbon fibers, thereby improving the electromagnetic shielding performance of the corresponding composite materials. For example, chemically plating high conductive coatings such as nickel and copper on the surface of carbon fibers, or spraying conductive coatings such as carbon nanotubes, graphene and silver. It should be pointed out that when the thickness of the conductive coating is too thin, the coating is often discontinuous and it is difficult to form an effective conductive path on the surface, so that the improvement of the conductivity of the composite material is not obvious; when the coating is thicker, it is difficult for the resin to infiltrate the conductive coating, which will cause a sharp decrease in the shear strength between the layers of the composite material.

[0006] The third method is to sandwich metal mesh, graphene film or carbon nanotube film between carbon fiber layers or attach it to the surface of carbon fiber composite materials to improve the conductivity of carbon fiber reinforced resin-based composite materials and thus improve their electromagnetic shielding performance. Compared with the first two methods, this method has significantly improved the conductivity and electromagnetic shielding performance of the composite material due to the introduction of a highly conductive interconnect. However, there are still many problems. The poor compatibility between the metal mesh and the resin matrix results in weak interfacial bonding between the two; and the high density of the graphene film and the carbon nanotube film makes it difficult for the polymer matrix to fully infiltrate them, which will cause a significant reduction in the mechanical properties of the carbon fiber composite material.

[0007] In recent years, studies have shown that the three-dimensional continuous structure of graphene can construct an efficient thermal and electrical conductive network pathway inside the composite material, thereby effectively improving the electrical and thermal conductivity of the corresponding laminated composite material. The Chinese invention patent "A three-dimensional skeleton graphene foam modified laminated composite material and preparation method" (publication number CN103057221A) adopts the method of inserting and paving a thin layer of three-dimensional graphene foam between the layers and on the surface of a continuous carbon fiber laminated composite material to prepare a carbon fiber graphene laminated composite material, achieving a significant improvement in the electrical conductivity and thermal conductivity of the carbon fiber composite material. The Chinese invention patent "A method for strengthening and toughening a composite material" (publication number CN108943767B) introduces a three-dimensional continuous structure of graphene and a high-toughness soluble and fusible resin composite structure into the layers of a continuous carbon fiber laminated composite material, achieving a significant improvement in the electrical conductivity, thermal conductivity and toughness of the carbon fiber laminated composite material. However, when these structures are used to prepare structural / electromagnetic shielding integrated composite materials, the following problems still exist: first, the surface of high-quality porous graphene is chemically inert and has poor compatibility with carbon fiber and polymer. It is difficult to obtain a good interface bonding by simply compounding it with a carbon fiber sandwich, which can easily lead to a decrease in the mechanical properties of the composite material, such as interlaminar shear strength; second, these inventions often only focus on improving the electrical conductivity of the carbon fiber composite system, lacking effective design and regulation of the electromagnetic shielding structure, especially the absorption and loss part, resulting in the reflection mechanism dominating the shielding effectiveness of the composite material, and the improvement in electromagnetic shielding performance is extremely limited. Summary of the invention

[0008] The main purpose of the present invention is to provide a method for preparing a structure / electromagnetic shielding integrated hybrid composite material to obtain a carbon fiber reinforced resin-based composite material with both high electromagnetic shielding effectiveness and high mechanical properties.

[0009] In order to achieve the above technical objectives, the technical solution proposed by the present invention is:

[0010] A method for preparing a structural / electromagnetic shielding integrated hybrid composite material, which uses a high-quality graphene three-dimensional network as a basic building unit, grows zinc oxide nanowires on its surface, and obtains a zinc oxide / graphene three-dimensional network hybrid composite material, which is then stacked and laid with carbon fiber cloth, and is molded by resin infusion to obtain a layered multi-scale hybrid composite material with a highly oriented structure.

[0011] The method for preparing the structure / electromagnetic shielding integrated hybrid composite material, the high-quality graphene three-dimensional network is prepared by chemical vapor deposition, hydrothermal method, self-assembly method, ice template method or template coating method, and the density is 5mg / cm 3 ~50mg / cm 3 , thickness is 1mm~5mm, conductivity is 0.5S / cm~30S / cm, porosity is 90%~99%, and C / O atomic ratio is 5~30.

[0012] In the preparation method of the structural / electromagnetic shielding integrated hybrid composite material, the zinc oxide nanowires on the surface of the graphene three-dimensional network are grown and prepared by a hydrothermal method, a chemical vapor deposition method or a sol-gel method, and the zinc oxide nanowires have a wurtzite structure, a diameter of 40nm to 200nm, and a height of 1μm to 3μm.

[0013] The preparation method of the structural / electromagnetic shielding integrated hybrid composite material is as follows: the inner layer of the zinc oxide / graphene three-dimensional network hybrid composite material is a graphene three-dimensional network, the zinc oxide nanowire array grows on the surface of the graphene network to form a coating layer, the weight ratio of zinc oxide to graphene is 4:1-2:1, the thickness of the zinc oxide / graphene three-dimensional network hybrid composite material is 1.005mm-5.005mm, and the thickness of the coating layer is 1μm-5μm.

[0014] The preparation method of the structure / electromagnetic shielding integrated hybrid composite material, the carbon fiber cloth layer is one or a combination of orthogonal cloth, unidirectional cloth, twill cloth, each layer of carbon fiber cloth has a thickness of 0.2mm to 1mm, a carbon fiber diameter of 1μm to 10μm, a single fiber number of carbon fiber tows of 1K to 48K, and a density of 1.5g / cm 3 ~2.0g / cm 3 .

[0015] In the preparation method of the structural / electromagnetic shielding integrated hybrid composite material, the zinc oxide / graphene three-dimensional network hybrid composite material layer is distributed between any two adjacent carbon fiber cloth layers, and the ratio of the number of carbon fiber cloth layers to the zinc oxide / graphene three-dimensional network hybrid composite material layers is (1-5):1.

[0016] The resin matrix used in the method for preparing the structure / electromagnetic shielding integrated hybrid composite material is a polymer matrix material with good flowability at room temperature or high temperature, such as epoxy resin, phenolic resin, polyimide resin or bismaleimide resin.

[0017] The preparation method of the structure / electromagnetic shielding integrated hybrid composite material is formed by a vacuum assisted resin transfer molding process, a resin transfer molding process, an autoclave molding process, a compression molding process or a hand lay-up molding process.

[0018] The design concept of the present invention is:

[0019] In view of the problem that it is difficult to achieve significant enhancement of the electromagnetic shielding effectiveness and mechanical properties of carbon fiber reinforced resin-based composite materials with existing methods, the present invention proposes to use a high-quality graphene three-dimensional network as a basic building unit, and in situ grow zinc oxide nanowires on its surface. The zinc oxide / graphene three-dimensional network hybrid composite material layer is laid between the carbon fiber layers as a functional layer to obtain a multi-scale hybrid composite reinforcement, and then resin infusion molding is performed to obtain a layered multi-scale hybrid composite material with a multiple reflection structure. The present invention gives full play to the significant advantages of high conductivity, large effective reflection area, and flexibility and light weight of the continuous graphene three-dimensional network, and combines the excellent dielectric loss characteristics and micro-nanostructure characteristics of zinc oxide nanowires. Through microstructure and micro-interface regulation, the electromagnetic reflection loss, absorption loss and multiple reflection loss mechanism of the composite material system are optimized, and a multi-scale hybrid advanced composite material with both high electromagnetic shielding effectiveness and high mechanical properties is obtained.

[0020] The advantages and beneficial effects of the present invention are:

[0021] 1. The present invention gives full play to the advantages of high conductivity and large effective reflection area of ​​high-quality graphene three-dimensional network. By modifying zinc oxide nanowires with dielectric loss characteristics on its surface, a zinc oxide / graphene three-dimensional network hybrid composite material is obtained, and then it is layered with carbon fiber cloth to construct a highly oriented layered multi-scale hybrid structure with multiple electromagnetic wave reflection layers and multiple absorption layers, which effectively realizes the electromagnetic shielding performance of carbon fiber composite materials, especially the enhancement of absorption efficiency. While meeting the current requirements of high-efficiency electromagnetic shielding, it effectively avoids the problem of secondary pollution. In addition, the zinc oxide nanowires grown in situ on the surface of the graphene three-dimensional network improve the surface inertness of the graphene three-dimensional body on the one hand, which is conducive to the full impregnation of the resin; on the other hand, the oriented zinc oxide nanowires form a mechanical interlocking bridge microstructure between the graphene three-dimensional body and the polymer, which enhances the interface bonding between the graphene three-dimensional body and the polymer, thereby significantly improving the mechanical properties of the carbon fiber composite material.

[0022] 2. The present invention achieves the simultaneous improvement of electromagnetic shielding effectiveness and mechanical properties of carbon fiber laminate composite materials by organically combining highly conductive continuous graphene three-dimensional bodies with highly electromagnetically absorbing zinc oxide nanowires, as well as comprehensive regulation of the composite material's micro-nanostructure and electromagnetic shielding mechanism. The composite material was tested for electromagnetic shielding performance, and its electromagnetic shielding performance was 40dB to 70dB, and its absorption efficiency was 30dB to 50dB. The composite material was tested for mechanical properties, and the tensile strength was 450MPa to 850MPa, the tensile modulus was 35GPa to 65GPa, the flexural strength was 450MPa to 850MPa, the flexural modulus was 35GPa to 65GPa, and the interlaminar shear strength was 35MPa to 65MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM photos of zinc oxide / graphene three-dimensional network hybrid composite materials; among them, (a) is a partial enlarged view of (b).

[0024] Figure 2 It is a schematic diagram of the vertical cross-sectional structure of the structural / electromagnetic shielding integrated hybrid composite material; in the figure, 1, carbon fiber cloth layer, 2, zinc oxide / graphene three-dimensional network hybrid composite material layer. DETAILED DESCRIPTION

[0025] The present invention is described in more detail below in conjunction with the embodiments. The following are only preferred embodiments of the present invention, and do not limit the scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the scope of the present invention.

[0026] In the specific implementation process, the present invention uses a high-quality graphene three-dimensional network as the basic building unit, grows zinc oxide nanowires on its surface, obtains a multi-scale hybrid composite material, and then stacks and lays it with carbon fiber cloth, and obtains a layered multi-scale hybrid composite material with a highly oriented structure through resin infusion molding.

[0027] Below, the present invention is further described in detail by examples.

[0028] Example 1

[0029] In this embodiment, the specific preparation parameters of the zinc oxide / graphene / carbon fiber composite material are:

[0030] The graphene three-dimensional network uses graphene foam prepared by chemical vapor deposition with a density of 10 mg / cm 3 , thickness is 1mm, conductivity is 7S / cm, porosity is 98%, and C / O atomic ratio is 25.

[0031] The zinc oxide nanowires were grown on the surface of the graphene three-dimensional network by a hydrothermal method to prepare a zinc oxide / graphene three-dimensional network hybrid composite material, with a weight ratio of zinc oxide to graphene of 3:1. Figure 1 As shown, the inner layer of the zinc oxide / graphene three-dimensional network hybrid composite material is a graphene three-dimensional network, and the zinc oxide nanowire array grows on the surface of the graphene network to form a coating layer with a thickness of 1.5μm to 2μm. The prepared zinc oxide nanowire has a wurtzite structure with a diameter of 50nm to 80nm and a height of 1.5μm to 2μm.

[0032] The carbon fiber cloth layer uses T700 orthogonal cloth. The thickness of each carbon fiber cloth layer is 0.5mm, the diameter of the carbon fiber is 7μm, the number of single fibers in the carbon fiber tow is 12K, and the density is 1.8g / cm 3 .

[0033] like Figure 2 As shown, four layers of carbon fiber cloth layers 1 and three layers of zinc oxide / graphene three-dimensional network hybrid composite material layers 2 are stacked and laid, wherein the upper and lower surfaces are carbon fiber cloth layers 1, and the zinc oxide / graphene three-dimensional network hybrid composite material layers 2 are sandwiched between any two layers of carbon fiber cloth layers 1.

[0034] The epoxy resin is used as the matrix and mixed with an amine curing agent. The laminated material is infused by a vacuum-assisted resin transfer molding process, and the laminated material is cured according to the curing process specified by the epoxy resin to obtain a structural electromagnetic shielding integrated hybrid composite material. Since the vacuum bag has a compression effect on the horizontally laminated zinc oxide / graphene foam layer and the carbon fiber cloth layer, the thickness of the obtained structural electromagnetic shielding integrated hybrid composite material is 2.4mm.

[0035] The electromagnetic shielding performance test of the composite material was carried out, and the electromagnetic shielding performance of the composite material was 70dB, and the absorption efficiency was 50dB. In addition, the mechanical performance test of the composite material was carried out, and the tensile strength of the composite material was 700MPa, the tensile modulus was 60GPa, the bending strength was 600MPa, the bending modulus was 60GPa, and the interlaminar shear strength was 50MPa.

[0036] Example 2

[0037] In this embodiment, the specific preparation parameters of the zinc oxide / graphene / carbon fiber composite material are:

[0038] The graphene three-dimensional network uses graphene foam prepared by chemical vapor deposition with a density of 8 mg / cm 3 , thickness is 1mm, conductivity is 6S / cm, porosity is 99%, and C / O atomic ratio is 15.

[0039] Zinc oxide nanowires were grown on the surface of a three-dimensional graphene network by a hydrothermal method to prepare a zinc oxide / graphene three-dimensional network hybrid composite material, with a mass ratio of zinc oxide to graphene of 2: 1. The inner layer of the zinc oxide / graphene three-dimensional network hybrid composite material is a three-dimensional graphene network, and the surface layer is a coating layer of a zinc oxide nanowire array, with a coating layer thickness of 1 μm to 1.5 μm. The prepared zinc oxide nanowires have a wurtzite structure, a diameter of 40 nm to 60 nm, and a height of 1 μm to 1.5 μm.

[0040] The carbon fiber cloth layer uses T300 orthogonal cloth. The thickness of each carbon fiber cloth layer is 0.4mm, the diameter of the carbon fiber is 7μm, the number of single fibers in the carbon fiber tow is 12K, and the density is 1.76g / cm 3 .

[0041] like Figure 2 As shown, four layers of carbon fiber cloth layers 1 and three layers of zinc oxide / graphene three-dimensional network hybrid composite material layers 2 are stacked and laid, wherein the upper and lower surfaces are carbon fiber cloth layers 1, and the zinc oxide / graphene three-dimensional network hybrid composite material layers 2 are sandwiched between any two layers of carbon fiber cloth layers 1.

[0042] The epoxy resin is used as the matrix and mixed with an amine curing agent. The laminated material is infused by a vacuum-assisted resin transfer molding process, and the laminated material is cured according to the curing process specified by the epoxy resin to obtain a structural electromagnetic shielding integrated hybrid composite material. Since the vacuum bag has a compression effect on the horizontally laminated zinc oxide / graphene foam layer and the carbon fiber cloth layer, the thickness of the obtained structural electromagnetic shielding integrated hybrid composite material is 2.0 mm.

[0043] The composite material was tested for electromagnetic shielding performance, and the electromagnetic shielding performance of the composite material was 65dB, and the absorption efficiency was 45dB. In addition, the composite material was tested for mechanical properties, and the tensile strength of the composite material was 650MPa, the tensile modulus was 55GPa, the bending strength was 550MPa, the bending modulus was 50GPa, and the interlaminar shear strength was 45MPa.

[0044] The implementation results show that the present invention gives full play to the significant advantages of high-quality continuous graphene three-dimensional network, such as high electrical conductivity, large effective reflection area, flexibility and light weight, and combines the excellent dielectric loss characteristics and micro-nano structural characteristics of zinc oxide nanowires to obtain a multi-scale hybrid composite material with high shielding effectiveness and excellent mechanical properties through structural arrangement orientation and interface regulation.

Claims

1. A method for preparing a structural / electromagnetic shielding integrated hybrid composite material, characterized in that: Using high-quality graphene three-dimensional network as the basic building unit, zinc oxide nanowires are grown on its surface to obtain zinc oxide / graphene three-dimensional network hybrid composite materials, which are then stacked and laid with carbon fiber cloth, and then resin infused to obtain a layered multi-scale hybrid composite material with a highly oriented structure; The inner layer of the zinc oxide / graphene three-dimensional network hybrid composite material is a graphene three-dimensional network, and the zinc oxide nanowire array grows on the surface of the graphene network to form a coating layer. The weight ratio of zinc oxide to graphene is 4:1 to 2:

1. The thickness of the zinc oxide / graphene three-dimensional network hybrid composite material is 1.005 mm to 5.005 mm, and the thickness of the coating layer is 1 μm to 5 μm. By organically combining highly conductive continuous graphene three-dimensional bodies with highly electromagnetically absorbing zinc oxide nanowires, as well as comprehensively regulating the micro-nanostructure and electromagnetic shielding mechanism of the composite material, the electromagnetic shielding effectiveness and mechanical properties of the carbon fiber laminated composite material are simultaneously improved; the electromagnetic shielding performance of the composite material is tested, and its electromagnetic shielding performance is 40dB to 70dB, and the absorption efficiency is 30dB to 50dB; the mechanical property test of the composite material is carried out, and the tensile strength is 450MPa to 850MPa, the tensile modulus is 35GPa to 65GPa, the bending strength is 450MPa to 850MPa, the bending modulus is 35GPa to 65GPa, and the interlaminar shear strength is 35MPa to 65MPa.

2. The method for preparing the structural / electromagnetic shielding integrated hybrid composite material according to claim 1, characterized in that: High-quality graphene three-dimensional networks are prepared by chemical vapor deposition, hydrothermal method, self-assembly method, ice template method or template coating method with a density of 5 mg / cm 3 ~50mg / cm 3 , thickness is 1mm~5mm, conductivity is 0.5S / cm~30S / cm, porosity is 90%~99%, and C / O atomic ratio is 5~30.

3. The method for preparing the structural / electromagnetic shielding integrated hybrid composite material according to claim 1, characterized in that: The zinc oxide nanowires on the surface of the graphene three-dimensional network are grown and prepared by a hydrothermal method, a chemical vapor deposition method or a sol-gel method. The zinc oxide nanowires have a wurtzite structure, a diameter of 40nm to 200nm, and a height of 1μm to 3μm.

4. The method for preparing the structural / electromagnetic shielding integrated hybrid composite material according to claim 1, characterized in that: The carbon fiber cloth layer is one or a combination of orthogonal cloth, unidirectional cloth, twill cloth, each layer of carbon fiber cloth has a thickness of 0.2mm to 1mm, a carbon fiber diameter of 1μm to 10μm, a single fiber number of carbon fiber tow of 1K to 48K, and a density of 1.5g / cm 3 ~2.0g / cm 3 .

5. The method for preparing the structural / electromagnetic shielding integrated hybrid composite material according to claim 1, characterized in that: The zinc oxide / graphene three-dimensional network hybrid composite material layer is distributed between any two adjacent carbon fiber cloth layers, and the ratio of the carbon fiber cloth layer to the zinc oxide / graphene three-dimensional network hybrid composite material layer is (1-5):

1.

6. The method for preparing the structure / electromagnetic shielding integrated hybrid composite material according to claim 1, characterized in that: The resin matrix used is a polymer matrix material with good fluidity at room temperature or high temperature, and is epoxy resin, phenolic resin, polyimide resin or bismaleimide resin.

7. The method for preparing the structure / electromagnetic shielding integrated hybrid composite material according to claim 1, characterized in that: The molding method is vacuum assisted resin transfer molding process, resin transfer molding process, autoclave molding process, compression molding process or hand lay-up molding process.

Citation Information

Patent Citations

  • A method for strengthening and toughening composite materials

    CN108943767B

  • Three-dimensional skeleton graphene foam modified laminated composite and preparation method thereof

    CN103057221A